EFFECTIVENESS OF STAD LEARNING MODEL WITH PULMAN MEDIA ON STUDENTS' UNDERSTANDING OF MATHEMATICAL CONCEPTS - Sabiela, Royana Nafisa; Zuliana, Eka; Ardianti, Sekar Dwi (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2025)
The background of this study is the low ability to understand mathematical concepts of fourth grade students of SDN 1 Damarjati which is evidenced by the provision of questions about understanding mathematical concepts. This study aims to determine the effectiveness of students' ability to understand mathematical concepts through the application of the STAD learning model assisted by PULMAN media. This study uses a quantitative experimental method with a pre-experimental design. The type of research used is one group pretest-posttest design. The population of the study was 36 fourth grade students of SDN 1 Damarjati. Sampling using saturated sampling techniques. Data collection techniques include interviews, observations, tests, and documentation, while data analysis is carried out using normality tests and N-Gain tests. The results of the N-Gain test analysis showed an increase with an average value of 0.59 with a moderate category. Meanwhile, the results of the N-Gain percent obtained an average of 59.9071 which was interpreted in the fairly effective category. Based on these results, it can be concluded that the application of the STAD learning model assisted by PULMAN media is effective in improving students' understanding of mathematical concepts.